2014
DOI: 10.1098/rsos.140095
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive nowcasting of influenza outbreaks using  Google searches

Abstract: Seasonal influenza outbreaks and pandemics of new strains of the influenza virus affect humans around the globe. However, traditional systems for measuring the spread of flu infections deliver results with one or two weeks delay. Recent research suggests that data on queries made to the search engine Google can be used to address this problem, providing real-time estimates of levels of influenza-like illness in a population. Others have however argued that equally good estimates of current flu levels can be fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
106
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 27 publications
1
106
0
Order By: Relevance
“…The increasing pervasiveness of always-on technology creates a vast amount of information that closely reflects human activity. This provides insight into the behaviour of people across the levels of their environment, from the individual scale, through groups and communities, to the global sphere, enabling the creation of models with predictive power [35]. Data recorded from mobile phones are a target of choice for research of this kind, offering a high granularity and being effectively ubiquitous in our society [612].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing pervasiveness of always-on technology creates a vast amount of information that closely reflects human activity. This provides insight into the behaviour of people across the levels of their environment, from the individual scale, through groups and communities, to the global sphere, enabling the creation of models with predictive power [35]. Data recorded from mobile phones are a target of choice for research of this kind, offering a high granularity and being effectively ubiquitous in our society [612].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of emerging opportunities, a potentially transformative one is seen in extending advanced spatial models in settings that use geo-referenced, real-time input data to make forecasts about current or near-future values (i.e., nowcasting [e.g., Lampos et al 2015, Preis andMoat 2014]). Recent years have seen a rapid growth of real-time data with location attributes, from Google's influenza reports (which exploit Internet users' search queries), through pedestrian or cyclist route and volume data collected from smart-phone applications (Smith 2015), to vehicle and driver information streamed from connected and instrumented vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in this area have demonstrated promising links between aggregate online behaviour and collective real world behaviour across a range of data sources such as the search engine Google [14][15][16][17][18][19][20][21], the search engine Yahoo! [22,23], the online encyclopedia Wikipedia [24][25][26][27][28], the microblogging platform Twitter [29][30][31][32][33][34] and the photosharing website Flickr [35,36].…”
Section: Introductionmentioning
confidence: 99%